The Application of Maqasid Shariah on Banking Industry - Aam Slamet Rusydiana; Mohammad Mahbubi Ali (Maqasid al-Shariah Review, 2022)
This research aims to determine the development map and the role of maqashid sharia in the banking industry based on Scopus indexed journals. The data analyzed includes 933 indexed research publications. The export data is then processed and analyzed using the R Biblioshiny application program to identify a bibliometric map of the development of the role of sharia maqashid in the banking industry. The results show that the number of publications regarding the development of the role of maqashid sharia research in the banking industry has increased significantly. The results also show that the most common type of document is journal articles. International Journal of the Analytic Hierarchy Process, Intellectual Discourse and 2nd International Symposium on Technology Management and Emerging Technologies, ISTMET 2015 - Proceedings is the journal that occupies the top position. The most famous author is Amin H, and the most popular keyword topic is Islamic banking. Then, the research cluster is based on the topic of maqashid on banking, including Islamic banking, Evaluation of sharia banking performance, CSR in Islamic Banking and Finance, and Maqashid Syariah on Islamic banking.